Assessment of Post-COVID-19 Syndrome and Its Relationship to Age, Sex, and Comorbid Disease in Iraqi Population - Noor Kadhim Mohamed-Jawad; Amal Malik Hassan; Safa Kifah Qasim (Medical Journal of Babylon)
Background: Post-coronavirus disease (post-COVID-19 syndrome) is any signs or symptoms that began during COVID-19 infection and persisted for at least 12 weeks after the first onset of infection. Objective: The study aimed to assess the post-COVID-19 symptoms in Iraqi patients and evaluate their incidence and relationships with patients’ age, sex, comorbid disease, and vaccination status. Materials and Methods: This was a cross-sectional study using well-designed questionnaires for recovered COVID-19 patients. The collected data were summarized and analyzed using a specific analytical program. Results: About 915 patients participated in the study, male 283 (30.9%) and female 632 (69.1%). About 619 (67.7%) of participants reported at least one post-COVID-19 symptom. Fatigue is the most common postviral symptom which occurs in 365 (39.9%) patients, followed by hair loss 286 (31.3%) and decreases in cognitive functions like forgetfulness 263 (28.7%) and decreased mental performance 248 (27%). The post-COVID-19 syndrome is significantly related to female gender, the severity of COVID-19, and preexisting comorbid diseases. In addition, this study found that the incidence of post-COVID-19 symptoms was significantly reduced after COVID-19 vaccination. Conclusion: Post-COVID-19 symptoms affect many patients after healing from acute infection and are mostly related to sex, the severity of coronavirus infection, and associated comorbidities. Follow-up may be required to minimize the effects of post-COVID-19 syndrome on general health and quality of life for affected patients.